Mekanisme Penggunaan Digipay sebagai Alat Pembayaran atas Belanja APBN di Kantor Pertanahan Kota Medan - Nasution, Arfiany Sepyanty Putri; Yusrizal, Yusrizal (IAI Nasional Laa Roiba Bogor, 2024)
The Ministry of Finance and Himbara Bank collaborated to develop Digipay Satu, a digital payment application system, with the goal of improving the efficiency and transparency of administering state finances. Within the Medan City Land Office, Digipay Satu serves as a shopping tool that unifies banking, MSMEs as suppliers of products and services, and APBN user spending units into a single ecosystem. This study examines the phenomena that arose during the Medan City Land Office's installation of Digipay Satu and analyzes the advantages, user flow, and implementation challenges of the system.